Is spinal surgery safe for elderly patients aged 80 and above? Predictors of mortality and morbidity in an Asian population - Tan, Joshua Yuan-Wang (2020)
Objective: We aimed to determine the 2-year mortality and morbidity rates following spine surgery in elderly patients (age ≥80 years) and to study the associated risk factors. Methods: The records of patients ≥80 years of age who underwent spine surgery during the years 2003–2015 at Tan Tock Seng Hospital, Singapore were retrospectively reviewed. Information was collected on their demographic characteristics, comorbidities, diagnosis, general and neurological status, type of surgery, and outcomes. The mortality and morbidity rates over a 2-year period were analyzed. Bivariate analyses were carried out to identify factors associated with mortality. Results: We selected 47 patients (mean age, 83.3 years; range, 80–91 years) who were followed up for a mean duration of 27.7 months. The mortality rates at 30 days, 6 months, 1 year, and 2 years following surgery were 2.1%, 8.5%, 10.6%, and 12.8%, respectively. The factors significantly associated with mortality included multiple comorbidities, nondegenerative aetiology, and vertebral fractures. The overall morbidity rate was 48.9%, and 17% of this cohort had major complications. Conclusion: Surgeons should strategize management protocols with due consideration of the mortality and morbidity rates, and be wary of operating on patients with multiple comorbidities, nondegenerative conditions, and vertebral fractures.